Penggunaan PEWS dalam Mengidentifikasi Kegawatan Pasien Anak di Unit Gawat Darurat - Siti Kusnul Khatimah; Dessie Wanda; Imami Nur Rachmawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the use of PEWS in identifying emergencies in pediatric patients in the emergency department and evaluating the degree of clinical deterioration in pediatric patients several hours before being in critical condition. The method used is a systematic review. The article search was adjusted to the research question formulation with the PICO formula using sources from the ScienceDirect, ClinicalKey and Google Scholar databases. The results showed that the use of PEWS was very effective in detecting emergencies in pediatric patients. PEWS can also determine the level of intervention and pediatric care. In conclusion, PEWS can be used as a monitoring tool because it can assist nurses in monitoring and controlling the child's condition to provide reports as quickly as possible to the doctor regarding the worsening of the child's condition. Keywords: Children, Clinical, PEWS, Review